Predictors of Direct Oral Anticoagulants Utilization for Thromboembolism Prevention in Atrial Fibrillation - Caroline Brais; Josiane Larochelle; Marie-Hélène Turgeon; Lucie Blais; Paul Farand; Sylvie Perreault; Geneviève Letemplier; Marie-France Beauchesne (Frontiers Media S.A., 2017)
PURPOSE: Several factors have been associated with the prescription of direct oral anticoagulants (DOAC) over warfarin such as younger age, fewer concomitant medications, and lower CHADS2 or bleeding scores. The primary objective of this study was to identify predictors of DOAC choice compared with warfarin for patients who are starting a new oral anticoagulant (OAC) for atrial fibrillation (AF). The secondary objective was to describe the proportion of DOAC prescriptions in new users of OAC for AF. METHODS: A retrospective cross-sectional study was conducted in a teaching hospital in Canada. Medical records of adult patients hospitalized in any medical units between October 1st, 2011 and October 1st, 2014, who were newly prescribed an OAC for non valvular AF were systematically reviewed. Baseline characteristics of warfarin and DOAC users were compared and a multivariate logistic regression analysis was completed to identify predictors of DOAC use. Variables included in the multiple regression analysis were: age, hypertension, diabetes, history of stroke or transient ischemic attack, coronary artery disease, peripheral arterial disease, CHADS2 score of 2 or more, creatinine clearance 30mL/min or more, polypharmacy, concomitant use of ASA or clopidogrel, and prescription by a neurologist. RESULTS: Among OAC users (144 patients on DOAC and 295 patients on warfarin), older age (odds ratio [OR] 0.97; 95%CI 0.95-0.98), peripheral arterial disease (OR: O.41;95%CI: 0.21-0.82), polypharmacy (OR: 0.30;95%CI:0.10-0.89), and concomitant use of clopidogrel (OR: 0.19;95%CI:0.07-0.56) decreased the probability of DOAC use. Prescription by a neurologist (OR: 2.77;95%CI:1.34-5.76) and an estimated creatinine clearance of at least 30mL/min (OR: 3.53;95%CI:1.18-10.57) increased the likelihood of DOAC prescription. CONCLUSION: To the best of our knowledge, this is the first observational study finding that concomitant use of clopidogrel reduced the likelihood of DOAC utilization while prescription by a neurologist increased the probability of receiving a DOAC over warfarin in patients with AF. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.